Bibliometric Analysis of Eco-Friendly Product Design - Loso Judijanto; Tati Handayani (Westscience Press, 2026)
This study conducts a bibliometric analysis of eco-friendly product design research to map its intellectual structure, collaboration patterns, and thematic evolution. Data were analyzed using keyword co-occurrence, co-authorship, country collaboration, and density visualization techniques. The findings reveal that the research field is primarily centered on “eco-friendly,” “product design,” and “sustainable development,” which serve as the core conceptual foundations. Emerging themes such as green chemistry, lifecycle assessment, circular economy, and materials performance indicate a shift toward more applied and technologically driven sustainability research. Temporal analysis further shows a transition from conceptual sustainability frameworks toward quantitative and experimental approaches in eco-design and product optimization. At the collaboration level, the co-authorship network demonstrates a relatively fragmented structure composed of several distinct research clusters with limited cross-group integration. However, certain authors and institutions act as bridging nodes that connect different clusters. At the country level, China and India emerge as dominant contributors and central hubs in global collaboration networks, while Europe maintains a stable secondary presence and other regions contribute in more peripheral but growing roles.